Public reactions to celebrity cancer disclosures via social media: Implications for campaign message design and strategy. - Pavelko, Rachelle L.; Myrick, Jessica Gall; Verghese, Roshni S.; Hester, Joe Bob (Health Education Journal, 2017)
Objective: The aim of this study was to analyse social media users’ reactions to a celebrity’s cancer announcement in order to inform future cancer-related campaigns. Design: A content analysis of Facebook users’ written responses to the actor Hugh Jackman’s 2013 post announcing his skin cancer diagnosis. Setting: Facebook’s application programming interface (API) software was used to compile all 14,534 comments posted by Facebook users under Jackman’s Facebook post between 21 November 2013 and 6 January 2014. Method: The Facebook API captured number of post likes and gender of the poster, while two trained coders also analysed the posts for emotional reactions, emoticon use and mentions of cancer-related behaviours. Results: Hope was the most common text-based emotional expression, and happy emoticons were the most used visual emotional expression in user comments in response to Jackman’s diagnosis. Posts mentioning detection behaviours were more likely to receive likes than those that did not mention them. Additionally, female users were significantly more likely to mention detection behaviours related to skin cancer than were male users. Conclusion: Celebrity cancer announcements may serve as de facto cancer awareness campaigns as well as highlight how to effectively craft coordinating strategic campaigns launched after a celebrity cancer disclosure.